Expression spectrum of new circFBN1 in various tissues and follicles of Taihang chicken - MA, TENG-HE; LI, MENG-XIAO; ZHANG, BEI-BEI; LI, XUE-NAN; WEI, JIA-RONG; WANG, HONG-NA; WANG, BIN; SHI, YU-XIANG (The Indian Journal of Animal Sciences, 2022)
In this study, the new circFBN1 derived from the FBN1 gene was identified. The expression spectrum of circFBN1 in various tissues and follicles of Taihang chickens was verified and analyzed. The effects on proliferation of GCs were checked. The results revealed that circFBN1 is indeed present and was differentially expressed in tissues and follicles and significantly promoted cell proliferation. In conclusion, our results suggested that circFBN1 could affect chicken follicular development by regulating the proliferation of GCs. These results will enable us recognize the molecular mechanisms in animal reproductive regulation.